Profit Optimization of Ngawen Orchid MSME - Ighfirli Amanda Izzati; Aida Haya Afifah; Neisya Jamilatus Syarifah; Wakhid Fitri Albar; Deddy Rahmadi (Universitas Negeri Padang, 2023)
The Ngawen Orchid MSME (Micro, Small, and Medium Enterprise) in Ngawen Hamlet, Ngawen Village, Muntilan District, Magelang Regency is a promising business opportunity. Apart from being in great demand, ornamental orchid plants also have a very high selling value. Orchid ornamental plants that are cultivated consist of three types: Dendrobium, Cattleya, and Phalaenopsis. This study aims to optimize profits by considering the number of plants and fertilizers used. This optimal profit can be achieved by applying the science of linear programming, one of which is the simplex method. The data collection techniques used in this study were interviews and direct observation of the Ngawen Orchid MSME. Based on the results of a linear programming analysis of the number of ornamental plants of Ngawen Orchid cultivation, optimal benefits were obtained from planting 40 Cattleya and 40 Phalaenopsis types orchids and there was no need to plant Dendrobium types, to get an optimal profit of IDR 4,600,000.